Der gebrochene Leib Christi: Ekklesiologische Impulse der Disability Theology für die Ökumene - Hamilton, Nadine (Evangelische Theologie, 2026)
The article reinterprets the Pauline image of the »body of Christ« through the lens of Disability Theology. Beginning from the wounded and risen Christ, it argues that fragility, dependency, and difference are constitutive dimensions of ecclesial life rather than deficits to be overcome. Christologically grounded in the unio hypostatica and communicatio idiomatum, divine presence is revealed in wounded embodiment. Ecclesiologically, the church appears as a communio vulnerata - a vulnerable, relational body sustained by mutual gift and recognition. Ecumenically, this perspective envisions unity through shared brokenness, where holiness is manifest not despite but through human limitation.